ELEKTRO PASTA KARBON TERMODIFIKASI HGO UNTUK ANALISIS ION PB2+ MENGGUNAKAN TEKNIK VOLTAMETRI LUCUTAN ANODIK GELOMBANG PERSEGI - Nurdiana, Geta
Carbon paste electrode has a wide range of application in voltametric analysis. This electrode is easy to be chemically modified to improve its sensitivity. In this research, carbon paste electrode modified with HgO has been made. The optimum composition for the paste is 5% mercury oxide, 20% paraffin, and 75% graphite. It perform better in KNO3 0,1M solution than HNO3 0,1M solution. The relative deviation standard is 2,77% for repeated measurement of 1 ppm Pb2+ solution. The calibration curve of Pb2+ solutions is linear in the concentration range of 10 ppb-10 ppm with detection limit of 2,4 ppb. Percent recovery of Pb2+ analysis is between 95,63 % to 100,20% showing good accuracy of this method.